Analysis of hair copper concentration in perimenopausal women - Wlaźlak, Edyta; Dunicz-Sokolowska, Aldona; Radomska, Krystyna; Stetkiewicz, Tomasz; Surkont, Grzegorz; Graczyk, Alfreda (Menopause Review/Przegląd Menopauzalny, 2007)
Analysis of concentrations of hair elements seems to be a promising method of initial health diagnostics. Copper plays a vital role in life processes. Aim of the study: The aim of the study was to define copper hair concentration in perimenopausal women. Material and methods: In this paper we analyzed the results of hair copper concentration in 258 Polish women aged 42-58. Results: Analysis of age tendencies shows a slight age-related decrease in copper concentration in the examined group of women. Conclusions: 1. Hair copper concentration in the examined group of perimenopausal women decreases with age. 2. Statistical analysis suggests that it is possible that copper deficiency exists in a relatively large part of the population of peri- and postmenopausal women.